Evaluación del clima laboral y su influencia en la calidad de atención al cliente en el GAD Municipal del cantón Junín - Cevallos Sánchez, Willians Jackson (2022)
The purpose of this research was to evaluate the work environment and its influence on the quality of customer service in the Municipal Autonomous Decentralized Government in Junín Canton. For the development of the project, three phases derived from the specific objectives set out in the study were contemplated, in the same way, the applied methodology was feasible a field and bibliographical investigation, in addition, to use methods and techniques that allowed the collection of information through of the interview and survey, considering that it began with the analysis and determination of the factors of the work environment, among which leadership, reward, equity, communication, participation, cooperation, commitment, teamwork, working conditions and training stand out. On the other hand, in the quality of the service, the dimensions of tangibility, reliability, response capacity, security and empathy were accentuated, elements that contributed to the achievement of the second stage, where it was detected that the working conditions, leadership, equipment and supplies and training show a regular assessment, in the same way, shortcomings were evidenced in the security variables in the provision of service. With this background, an improvement plan was proposed to help solve this problem, for this reason, actions were proposed through the 5w+1H matrix, which will be made available to the competent authorities. In conclusion, is deduced that the work environment of this public institution maintains an acceptable value scheme, so it is necessary to take measures that promote productive changes for the Municipal GAD in Junín Canton.